The long-term impact of adverse childhood experiences on episodic memory in mid- to late-life among US older adults. - Johnson, Kimson E.; Brown, Monique J. (Aging & Mental Health, 2026)
Objectives: Adverse childhood experiences (ACEs), including abuse, neglect, and household dysfunction, are associated with depression, substance use. While, prior research suggests ACEs influence memory, few studies have examined this relationship in a nationally representative sample of older US adults. This study explores associations between ACEs before 18 and mid- to late-life episodic memory. Methods: We conducted a secondary analysis of Health and Retirement Study data to assess ACEs and episodic memory in adults aged 51 and older. ACEs were measured as cumulative exposure to early adversity (repeating school, trouble with police, parental substance use, physical abuse). Episodic memory was assessed using total recall (immediate + delayed word recall). Group differences were examined using t-tests and chi-square tests. Linear regression models tested associations between ACE exposure (0, 1, 2, ≥3) and memory scores, adjusting for sociodemographic, childhood, and psychosocial factors. Results: Among 7568 participants, 2,768 (36.9%) reported ≥1 ACE; 187 (2.5%) reported ≥3. The mean total recall score was 10.31 ± 3.70. Exposure to ≥3 ACEs was associated with lower memory scores (β = −0.81, p < 0.05). Conclusions: Experiencing ≥3 ACEs before 18 was linked to poorer episodic memory, underscoring the value of trauma-informed strategies to support brain health.